The Impact of Cryptocurrency and Electronic Money Use On The Circulating Money Supply and Monetary Stability in Indonesia - Yolanda Sari; Etik Winarni (Nomico, 2024)
The purpose of this research is to analyze the long-term and short-term impacts of the use of cryptocurrency and electronic money on the money supply (M2) in Indonesia, as well as to analyze the long-term and short-term impacts of the use of cryptocurrency and electronic money on monetary stability (exchange rates) in Indonesia. The research method used is quantitative descriptive analysis with the Vector Error Correction Model (VECM) using the Eviews application and secondary data in the form of monthly data from 2011 to 2023 obtained from the official websites of Bank Indonesia and Finance. This study utilizes data on cryptocurrency transaction values and electronic money transaction values in Indonesia by analyzing the VECM model, which can observe the long-term and short-term impacts of the use of digital money on the money supply and monetary stability, in this case, viewed through the Indonesian exchange rate. The research results indicate that there is a one-way causality between electronic money and cryptocurrency, but not the other way around, and there is a one-way causality between the money supply and cryptocurrency, with the money supply as the dependent variable influencing cryptocurrency. The results of the VECM estimation indicate that in the long term, electronic money has a negative and sifnificant impact on the money supply. Meanwhile, the short-term estimation shows that both cryptocurrency and electronic money significantly influence the money supply, but their effects are dynamic and vary based on different lags. The long-term estimation with the exchange rate as the dependent variable shows that cryptocurrency does not have a significant impact on the exchange rate, while in the short term, both cryptocurrency and electronic money have a negative and significant effect on the exchange rate.